Sodium channel blockers as add-on treatment for unexplained refractory chronic cough: a case report and review - Butnariu, I.; Balan, M.-F.; Zaharia, D. C.; Bobocea, R.; Mitrică, Iulia Ana-Maria; Moraru, A.; Dionisie, V.; Lăptoiu, Vlad-Iulian; Antonescu-Ghelmez, D.; Antonescu, F. (Frontiers in Medicine, 2026)
IntroductionChronic cough is a common symptom with multiple causes, predominantly respiratory, gastroesophageal, or neurological. However, in rare cases, a vascular anomaly, such as internal jugular vein ectasia (IJVE), may function as a trigger. We report the case of a patient with paroxysmal chronic cough associated with right internal jugular vein ectasia, which responded favorably to anticonvulsant therapy.Case reportWe present the case of a 62-year-old female patient with pulmonary, cardiovascular, and neurological comorbidities, with a two-year history of daily episodes of severe, non-productive cough, refractory to standard symptomatic treatments. ENT, pulmonary, and gastroenterological evaluations did not identify a specific organic cause. The neurological examination was unremarkable, with no cranial nerve deficits. Cervical CT with contrast revealed a fusiform right internal jugular vein ectasia (IJVE) (area of 2.11 cm2 compared to the left side, 0.50 cm2). A chronic neurogenic cough possibly linked to the IJVE was suspected, and treatment with carbamazepine (300 mg three times daily) and codeine (15 mg four times daily) was successful in near-complete cough suppression.ConclusionThis case adds to the emerging evidence regarding a possible link between IJVE and chronic neuropathic cough. Although rare, this etiology should be considered in chronic cough syndromes without an apparent cause. Neuropathic cough is underdiagnosed and may benefit from anticonvulsant treatment, while the identification of atypical mechanisms requires a multidisciplinary approach.